CONCEPTUAL FRAMEWORK FOR UNDERSTANDING EMERGING TECHNOLOGIES THAT SHAPE THE ACCOUNTING AND ASSURANCE PROFESSION OF THE FUTURE - Atanasovski, Atanasko; Bozhinovska lazarevska, Zorica; Trpeska, Marina (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
We are currently on the verge of the fourth industrial revolution (industry 4.0) that will fundamentally change the way in which businesses and individuals operate. It is characterized by the integration of both physical and virtual world with a new pulse for greater automation and autonomy of business processes without or limited need of human intervention. Cloud computing, the internet of things, big data and data analytics, artificial intelligence and machine learning, blockchain, augmented reality are among the most exploited contributing technologies. This paper provides a conceptual framework for emerging technologies with greatest disruptive potential for the accounting and assurance profession. We have surveyed the scarce literature with the aim of investigating the relationship and interplay between most potent emerging technologies and accounting and assurance services. Our findings suggest that cloud accounting, big data, blockchain, artificial intelligence and machine learning will most likely shape the accounting and assurance world for many organisations and future skills set pursued by professionals in order to add value. We conclude that current accounting research efforts are insufficient to understand and grasp the possible future interactions between the vibrant digital economy, its emerging technologies and the accounting profession, including the changing information needs of investors.
Keywords: big data; blockchain; accounting; emerging technologies; cloud